2014
DOI: 10.3892/mmr.2014.2675
|View full text |Cite
|
Sign up to set email alerts
|

miR-143 inhibits cell proliferation by targeting autophagy-related 2B in non-small cell lung cancer H1299 cells

Abstract: microRNAs (miRNAs) are small, non‑coding RNAs involved in multiple biological pathways by regulating post-transcriptional gene expression. Previously, autophagy has been reported to suppress the progression of non-small cell lung cancer (NSCLC). However, how miRNAs regulate autophagy in NSCLC remains to be elucidated. In the present study, the autophagy gene, autophagy-related 2B (ATG2B), was identified as a novel target of miR-143. The overexpression of miR-143 was able to downregulate the expression of atg2b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(52 citation statements)
references
References 29 publications
0
48
0
4
Order By: Relevance
“…Member(s) of the hsa-miR-18114 and hsa-miR-29 families15 exhibit both anticancer and pro-cancer regulation under different clinical conditions, while members of hsa-miR-12616, hsa-miR-12917, hsa-miR-13618, hsa-miR-20419, hsa-miR-66320, hsa-miR-9921, hsa-miR-37822, hsa-miR-9223, and hsa-miR-40924 families are recognized as having anticancer properties under different clinical conditions. Families that contained at least one miRNA found in hAMSC-CM-derived exosomes reportedly exhibit antagonistic roles in numerous cancer types and include hsa-miR-48625, hsa-miR-10026, hsa-miR-10127, hsa-miR-12428, hsa-miR-128529, hsa-miR-13430, hsa-miR-13831, hsa-miR-13932, hsa-miR-14333, hsa-miR-18634, hsa-miR-19335, hsa-miR-20536, hsa-miR-22237, hsa-miR-33838, hsa-miR-33939, hsa-miR-42440, hsa-miR-12741, hsa-miR-2642, hsa-miR-10343, hsa-miR-10744, hsa-miR-12845, hsa-miR-14046, hsa-miR-14447, hsa-miR-15348, hsa-miR-19249, hsa-miR-21250, hsa-miR-21851, hsa-miR-2352, hsa-miR-2553, hsa-miR-37054, hsa-miR-37555, hsa-miR-38156, hsa-miR-41057, hsa-miR-4158, and hsa-miR-9359. These NGS data revealed an enriched miRNA population in hAMSC-CM-derived exosomes that are likely involved in the regulation of different types of cancer.…”
Section: Resultsmentioning
confidence: 99%
“…Member(s) of the hsa-miR-18114 and hsa-miR-29 families15 exhibit both anticancer and pro-cancer regulation under different clinical conditions, while members of hsa-miR-12616, hsa-miR-12917, hsa-miR-13618, hsa-miR-20419, hsa-miR-66320, hsa-miR-9921, hsa-miR-37822, hsa-miR-9223, and hsa-miR-40924 families are recognized as having anticancer properties under different clinical conditions. Families that contained at least one miRNA found in hAMSC-CM-derived exosomes reportedly exhibit antagonistic roles in numerous cancer types and include hsa-miR-48625, hsa-miR-10026, hsa-miR-10127, hsa-miR-12428, hsa-miR-128529, hsa-miR-13430, hsa-miR-13831, hsa-miR-13932, hsa-miR-14333, hsa-miR-18634, hsa-miR-19335, hsa-miR-20536, hsa-miR-22237, hsa-miR-33838, hsa-miR-33939, hsa-miR-42440, hsa-miR-12741, hsa-miR-2642, hsa-miR-10343, hsa-miR-10744, hsa-miR-12845, hsa-miR-14046, hsa-miR-14447, hsa-miR-15348, hsa-miR-19249, hsa-miR-21250, hsa-miR-21851, hsa-miR-2352, hsa-miR-2553, hsa-miR-37054, hsa-miR-37555, hsa-miR-38156, hsa-miR-41057, hsa-miR-4158, and hsa-miR-9359. These NGS data revealed an enriched miRNA population in hAMSC-CM-derived exosomes that are likely involved in the regulation of different types of cancer.…”
Section: Resultsmentioning
confidence: 99%
“…A recent study has revealed that miR-143 inhibits NSCLC cell proliferation by targeting the autophagy gene, autophagy-related 2B [45]. HMGB1 is present at increased levels in NSCLC patients [46].…”
Section: Discussionmentioning
confidence: 99%
“…Discussion miR-143 is located in the chromosome 5 with a mature length of 22 [10]. A previous study has revealed that miR-143 exhibited down-regulation in many cancers such as colorectal cancer [11], pancreatic cancer [12] and lung cancer [13] in which miR-143 acts as a tumor suppressor inhibiting cell proliferation and inducing tumor cell apoptosis thus hindering the development of cancer [10]. miR-143 was exploited in many cancers e.g.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand; this could also be explained by the hepatocyte destruction due to the HCC and hence higher level in the blood. Autophagy gene 2B (ATG2B) was found to be a possible target for miR-143, where miR-143 Overexpression is associated with down regulation of ATG2B [13]; thus decreasing the autophagy responsible for the cancer cell survival and inducing apoptosis [20].…”
Section: Resultsmentioning
confidence: 99%